CREATIVEPRENEUR ON SEKOPERPROJECT : WOMEN EMPOWERMENT PROGRAM FOR ECONOMIC EMANCIPATION - Eka Srirahayu Ariestiningsih; Genoveva Genoveva; Dwi Faqihatus Syarifah Has (President University, 2021)
The aim of this research is to find out how to improve the quality of life of SEKOPER members to become creativepreneur, which is a form of women's empowerment program for economic emancipation. This is program for gender equality and justice, developing and strengthening women's knowledge and learn poverty alleviation as the social protection programs, which is organized by Gresik Regency Government because many women dropped out of school and un-productive. According to data from the Central Statistics Bureau, the female unemployment in 2019 it increased significantly to 5.92%.To achieve this goal, researchers used a qualitative method, with primary and secondary sources as data collection instruments, namely observation, in-depth interviews, and using the Participatory Rural Appraisal approach. Based on the analyzed data, the research findings that SEKOPER members have succeeded in becoming creativepreneur with : 1) Facilities and policy from Head of village as the Regional Government, 2) Coaching from UMG as a higher education institution that provides innovative healthy food and how to market the products and 3) Sponsorship by Combined Cycle Power Plant (PJB) as their CSR program. The success of developing an innovative healthy food business, it will improve the economy of the family and the region, which is form of economic emancipation. Keywords : SEKOPER, Women Empowerment, Economic Emancipation